Interface shear properties of geosynthetics and construction and demolition waste from large-scale direct shear tests - Castorina S. Vieira (2016)
In recent years environmental sustainability has demanded a progressive increase of waste recycling in general and waste value-added utilisation in the construction industry in particular. As regards the application of construction and demolition wastes (C&DW) in geotechnical works, it has been noticed that the use of recycled aggregates is found mostly in road construction. Value-added utilisation of C&DW in geosynthetic-reinforced structures is almost an unexplored field. This paper presents the results of physical, mechanical and environmental characterisation of recycled C&DW, as well as the direct shear behaviour of three recycled C&DW-geosynthetic interfaces. The C&DW material was collected from a recycling plant and came from the demolition of single-family houses and the cleaning of land with illegal deposits of C&DW. Two geogrids and one geocomposite reinforcement (high-strength geotextile) were used to assess the behaviour of C&DW-geosynthetic interfaces. The environmental characterisation of the C&DW, carried out through leaching tests, did not show environmental concerns. Direct shear test results have demonstrated that properly selected and compacted C&DW can exhibit shear strength similar to natural soils. The coefficients of interaction achieved for C&DW-geosynthetic interfaces compare well with those reported in the literature for soil-geosynthetic interfaces under similar conditions, which supports the feasibility of using these recycled materials as backfill in geosynthetic-reinforced structures.